Reproductive and developmental effects of carbon nanotube exposure: A systematic review - Arianti, Santi Febri (Institute of Computer Science (IOCS), 2025)
Carbon nanotubes (CNTs) are nanoscale materials widely utilized in medical and industrial fields due to their unique physicochemical properties. However, growing exposure to CNTs—particularly during pregnancy—has raised concerns about their potential impact on reproductive health and fetal development. This review aims to identify and evaluate scientific evidence on the effects of CNT exposure on reproductive systems, pregnancy outcomes, and fetal development in both humans and animals, while also exploring the underlying biological mechanisms. A systematic review was conducted in accordance with the PRISMA 2020 guidelines. Literature searches were performed across PubMed, Scopus, Web of Science, and Google Scholar using combinations of keywords related to CNTs, pregnancy, fertility, and toxicity. Articles that met the inclusion criteria were screened and analyzed narratively according to thematic outcomes. Study quality was assessed using the SYRCLE and Newcastle-Ottawa Scale tools. A total of 43 studies were included. CNT exposure was associated with disrupted reproductive cycles, reduced sperm quality, miscarriage, placental dysfunction, and fetal developmental abnormalities. The primary mechanisms involved oxidative stress, inflammation, hormonal disruption, and epigenetic alterations with transgenerational effects. CNTs have the potential to adversely affect reproductive health and fetal development. This review highlights the urgent need for awareness, protective regulations, and further research in human populations to reduce risks to maternal and child health in the context of expanding nanotechnology applications.